Expression of BRAF, EGFR and CD10 in ameloblastoma: Their potential role in local tumour invasiveness / Tan Chuey Chuan - Tan, Chuey Chuan (2017)
Objectives: The aim of the present study is to investigate the expression of BRAF, EGFR and CD 10 in ameloblastoma and determine the impact of these pro-invasive biomarkers on the biological behavior of different ameloblastoma subsets. Methods: BRAF, EGFR and CD10 expression were examined with immunohistochemical techniques in 39 cases of paraffin-embedded ameloblastoma [19 unicystic ameloblastoma (UA) and 20 solid/multicystic ameloblastoma (SMA)]. Semi-quantitative score method was used to evaluate the immunoexpression which classified into pre-ameloblast-like cells (PA-cells), stellate reticulum-like cells (SR-like) and stromal cells (ST-cell) in ameloblastoma. The study was approved by the Medical Ethic Committee, Faculty of Dentistry, University of Malaya [Ethics DF OS1502/0011(P)]. Findings: The pro-invasive markers were significantly expressed in all three localisation for both UA and SMA (P<0.05). Statistically significant differences in the expression of these markers between epithelial components and stromal cells were observed (P<0.05). Immunoreactivity of EGFR in SMA was associated with ethnicity (P<0.05). Conclusion: BRAF, EGFR and CD10 were significantly expressed in SMA and UA which indicating their active local bone activity in ameloblastoma. These findings suggest their potential roles as prognostic markers of ameloblastoma and targeted therapy could be considered to treat the advanced unresectable ameloblastoma. (PPPC/C1-2015/DGJ/02)